Applications for 5G Networks - PINTO, GABRIEL EDMILSON; Lopes Rosa, Renata; Zegarra Rodriguez, Demostenes (INFOCOMP Journal of Computer Science, 2021)
The communication media has undergone major technological advances in recent decades, from telegraph services to the internet of things. These rapid changes have impacted the routine of humanity and its way of seeing the world in an impactful way. Currently, we are entering the fifth generation (5G) of mobile telephony, whose architecture promises extensive exchanges of messages in a short period of time, which was still difficult to obtain in the networks of the previous generation. Given this new technology, this work proposes to investigate its impacts and possible advances in the area of Internet of Things, an emerging technology that extends mobile networks to so-called smart objects.